1996
DOI: 10.1097/00007632-199611150-00016
|View full text |Cite
|
Sign up to set email alerts
|

“Movement” in Work Status After Pain Facility Treatment

Abstract: Because chronic pain patients "move" in and out of employment and for work capacity status after pain facility treatment, future outcome studies using these measures will have to consider carefully the impact of "movement" on their results.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
15
0

Year Published

2000
2000
2013
2013

Publication Types

Select...
5
2

Relationship

1
6

Authors

Journals

citations
Cited by 19 publications
(18 citation statements)
references
References 14 publications
3
15
0
Order By: Relevance
“…Early rehabilitative interventions have been recommended for this group by several authors [16,17] with needs assessments as a starting point [28]. The present ndings suggest that the OTNA -PP may be used to discover unmet needs as part of needs assessments to enhance the effects of early rehabilitative interventions.…”
Section: Discussionmentioning
confidence: 92%
See 2 more Smart Citations
“…Early rehabilitative interventions have been recommended for this group by several authors [16,17] with needs assessments as a starting point [28]. The present ndings suggest that the OTNA -PP may be used to discover unmet needs as part of needs assessments to enhance the effects of early rehabilitative interventions.…”
Section: Discussionmentioning
confidence: 92%
“…Do you perform daily activities with greater effort compared with when 15 As above you did (do) not have pain? If you are on sick leave: do you consider it valuable to be at your 16 As above workplace and work without demands on work performance, in order to maintain contact with your work and:or to reduce passivity? Does your pain prevent you from living up to the existing expectations 17 As above on you at work (e.g.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Rehabilitation services might be more effective if people in need were referred to healthcare facilities without delay (Fishbain et al, 1996;Linton and Hallden, 1998). Whether patients are referred to occupational therapy depends on the doctor or healthcare case worker's knowledge about occupational therapy and current healthcare community policies (Andersson, 1997;Söderback et al, 2000).…”
Section: Introductionmentioning
confidence: 99%
“…Therefore, it is obvious that more outcome studies with appropriate control groups are necessary. A recent study by Fishbain et al (1996) has identified another possible confounder of this type of outcome research. CPPs were followed up after pain facility treatment as part of a study on the prediction of return to work.…”
Section: Future Research Initiativesmentioning
confidence: 99%